Formulasi Sediaan Kosmetik Facial wash Ekstrak Etanol Daun Kelor (Moringa oleifera L.) dengan Variasi Konsentrasi Sodium Lauryl Sulfat - Nur Azizah Syahrana; Suryanita Suryanita; Muhammad Asri SR; Indah Indah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Moringa leaves (Moringa oleifera L) contains tannins, flavonoids and sapoins compounds, that function as antibacterials. This study aims to formulate a facial wash preparation from the ethanol extract of Moringa leaves as a facial skin cleanser. The ethanol extract of Moringa leaves was made in the form of 3 facial wash preparation formulas with a concentration of 3%, and different Sodium lauryl sulfate, namely FI (1%), FII (1.5%) and FIII (2%). Prior to the formulation, Moringa leaves were macerated with 96% ethanol to obtain a thick extract. Then proceed with organoleptic testing, pH testing, homogeneity testing and foam height testing. The results of the study on the evaluation of facial wash preparations of ethanol extract of Moringa leaves FII and FIII with SLS concentrations of 1.5% and 2% showed the best formulation compared to F1